A comprehensive frame work for Aceh development under the role of Siyasah Shariyyah: a visionary Aceh development - Kayadibi, Saim; Kayadibi, Yasemin (2012)
Due to the strategic position and natural resources of Aceh province, foreign powers always kept their eyes on this area. It is a historically well-known reality that religious Acehnese people always straggled to protect their lands and natural resources in the province against foreign invaders since they have been very fond of their freedom and dignity. Therefore, the history of Aceh is full of straggles given against foreign occupiers. In that respect the province really needs serious projects and strategies in order to use its natural resources in an efficient way for the development of the area. Indonesia’s special province, Aceh, needs to implement these projects and strategies through economic, political and social co-operations with other countries especially Muslim countries. These projects can only be materialized via taking into the consideration of the universal values of Siyasah Shariyyah (Shariah oriented public policy). Therefore, this article tries to determine substantial ways for the development of Aceh province in terms of economic, political and social aspects. Keywords: Aceh Development; Shariah oriented public policy; Essential Values; OIC countries;